2010
DOI: 10.1016/j.appet.2010.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition knowledge, and use and understanding of nutrition information on food labels among consumers in the UK

Abstract: Based on in-store observations in three major UK retailers, in-store interviews (2019) and questionnaires filled out at home and returned (921), use of nutrition information on food labels and its understanding were investigated. Respondents' nutrition knowledge was also measured, using a comprehensive instrument covering knowledge of expert recommendations, nutrient content in different food products, and calorie content in different food products. Across six product categories, 27% of shoppers were found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

51
439
11
20

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 471 publications
(521 citation statements)
references
References 25 publications
51
439
11
20
Order By: Relevance
“…Previous studies showed that they differed in terms of market penetration, consumer acceptability and understanding, factors which might affect their use (4)(5)(6)(7)(8)(9) . Some works showed that, compared with simple formats like health logos, detailed FOP labels (i.e.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies showed that they differed in terms of market penetration, consumer acceptability and understanding, factors which might affect their use (4)(5)(6)(7)(8)(9) . Some works showed that, compared with simple formats like health logos, detailed FOP labels (i.e.…”
mentioning
confidence: 99%
“…'multiple traffic lights' and 'Guideline Daily Amounts') appear to be well accepted by consumers, probably due to more rapid and easier identification and use, along with more complete information (4,10,11) . In addition, previous studies suggested that most FOP labels are clearly understood (5)(6)(7) .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies also supported the importance of health-related aspects for label use (see references (1), (2) and (5) for reviews of this literature). For example, having a strong belief in a relationship between diet and cancer, interest in healthy eating and being confident that one is able to eat healthily were associated with whether participants used labels at all (11)(12)(13)(14) . Furthermore, Petrovici and Ritson (15) found that self-reported nutrition knowledge and health motivation were positively related to frequency of label use.…”
mentioning
confidence: 99%